Learning styles of ethnic minority students: a matched case-control study in a dental school in Latin America - Ardila Medina, Carlos Martín; Gómez Restrepo, Angela María (CES odontología, 2021)
Introduction and objective: Little is known about the learning styles of ethnic minorities in Latin American universities. The objective of this research was to identify the learning styles of the ethnic minorities attending a dental school. Moreover, their grade point averages were explored. Materials and methods: A total of 30 ethnic minority students were matched with 30 non-minority students. All the students took a systematized questionnaire to categorize their learning styles. Results: A strong association between ethnic minority students and low reflector style was observed in the multivariate model after adjusting for age, sex, and the current semester (OR=11; 95% CI=1.2-99; p=0.03). In addition, a relevant association between minority ethnic group and low theorist style was observed in the multivariate model after controlling for the same variables (OR= 4; 95% CI=1.2-11; p=0.02). Finally, a statistically significant difference was observed in the grade point averages of non-minority and minority groups, with the minority group having the loweraverages (p=0.014). Conclusions: Ethnic minority students presented lower means for all learning styles compared to the control group. Similarly, theirgrade point averages were significantly inferior. These findings represent relevant precedents for creating educational strategies to improve the learning of ethnic minority groups in higher education in Latin America.